Comparative study of some variables (skill performance, physical and motor abilities) before and after the league competitions for women's futsal players season 2023/2024 - ALATTAR, Samer (Journal of Physical Education, 2025)
This study aimed to identify the impact of the Iraqi Women's Futsal League competitions for the 2023-2024 season on the level of skill performance and some physical and motor abilities of the players participating in the league competitions, i.e. a comparison between before and after the league competitions, as pre- and post-tests were conducted on a sample of 45 players participating in the Iraqi League, and the researcher processed the results of the raw tests and the study reached the significance of the results in skill performance and physical and motor abilities, which confirms the positivity of the impact of the Iraqi League on the players. In addition, playing matches continuously helps in developing the skill performance of the players, and the researcher recommends that the training curricula for coaches in the preparation stages include intensive matches in order to raise physical and skill capabilities